Identification of biomolecules involved in the biosynthesis of gold nanoparticles from living peanut seedlings - Raju, D.; Siddiqui, Ejaz Ahmad; Prasanth, S.; Khan, Bashir M.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2017)
In present work, we have fabricated gold nanoparticles by treating an aqueous solution of 10(-4) M HAuCl4 with the proteins extracted from roots of in vitro raised peanut seedlings and purified them by FPLC at room temperature. These proteins which tested positive for the reduction of 10(-4) M HAuCl4 were identified as Mannose glucose binding lectin and Ara h 8 allergen isoforms by ESI MS/MS. It is a well known fact that aromatic amino acids possess delocalized pi electrons in their ring structures, rendering them as the best electron donors which can transfer electrons and reduce the acceptor. These results suggest that the aromatic amino acids present in the proteins from the peanut seedlings are the primary biomolecules involved in the reduction of Au (III) to Au (0). We isolated different protein of molecular weight 16.4, 28.3 and 30 kDa involved in the formation of nanoparticles. The protein with molecular weight 16.4 kDa (allergens) yielded NPs of 25-60 nm whereas, the proteins with molecular weight 28.3 kDa and 30 kDa (lectins) yielded highly monodispersed NPs of 5-20 nm in size. The results clearly indicate that the size of nanoparticles can be controlled by different proteins.